Measuring historical inequality in Africa: What can we learn from social tables? - Ellen Hillbom; Jutta Bolt; Michiel de Haas; Federico Tadei (African Economic History Network (AEHN), 2021)
Limited knowledge of African inequality trajectories hampers our understanding of the drivers of heterogeneous inequality outcomes in Africa today, and leads to a major omission in debates about global inequality. In recent years, African economic history has advanced towards the reconstruction of full income distributions of African economies using 'social tables'. In this paper, we take stock of the social table literature covering the cases of Botswana, Ghana, Ivory Coast, Kenya, Senegal, and Uganda, 1910s to 1960s. Our contribution is twofold. First, we investigate commensurability and pursue methodological harmonisation. Second, we propose a new analytical framework to study income inequality in colonial Africa, revolving around export-oriented commercialisation and colonialism. We apply this framework to the six cases. Tracing country-level inequality trends and levels using three different inequality metrics, we find that i) inequality increased as commercialisation progressed and ii) relative levels of inequality differed substantially and were linked to European settlers and colonial institutions. Using inequality decompositions by sector and race, we further refine these insights. We find that capital-intensive commodities were associated with larger inequality in the self-employed sector and that the presence of European settlers and a large colonial administration increased the salience of race as a major fault line.
Keywords: 330